2009
DOI: 10.1056/nejmoa0810625
|View full text |Cite
|
Sign up to set email alerts
|

Intensive versus Conventional Glucose Control in Critically Ill Patients

Abstract: Background The optimal target range for blood glucose in critically ill patients remains unclear. Methods Within 24 hours after admission to an intensive care unit(ICU), adults who were expected to require treatment in the ICU on 3 or more consecutive days were randomly assigned to undergo either intensive glucose control, with a target blood glucose range of 81 to 108 mg per deciliter(4.5 to 6.0 mmol per liter), or conventional glucose control, with a target of 180 mg or less per deciliter(10.0 mmol or less p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
1,054
9
33

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,212 publications
(1,130 citation statements)
references
References 33 publications
34
1,054
9
33
Order By: Relevance
“…The detrimental effects of glycemic disorder are not limited to stress hyperglycemia; they also include fluctuations of glycemic values, with acute glucose changes in both directions 35. Accordingly, it has been shown that intensive lowering of glycemia may have a detrimental effect in patients with high glycemic values at admission but without stress hyperglycemia 36, 37. In view of the close association between stress hyperglycemia and AKI risk, future studies should investigate whether tight control of hyperglycemia, based on the combined evaluation of acute and chronic glycemia, will prevent AKI and improve overall prognosis in AMI.…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effects of glycemic disorder are not limited to stress hyperglycemia; they also include fluctuations of glycemic values, with acute glucose changes in both directions 35. Accordingly, it has been shown that intensive lowering of glycemia may have a detrimental effect in patients with high glycemic values at admission but without stress hyperglycemia 36, 37. In view of the close association between stress hyperglycemia and AKI risk, future studies should investigate whether tight control of hyperglycemia, based on the combined evaluation of acute and chronic glycemia, will prevent AKI and improve overall prognosis in AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Normoglycaemia and whole body protein stores can be preserved by insulin therapy suggesting that insulin sensitivity rather than insulin responsiveness is reduced during and after surgery 54. Although the safety and efficacy of glucose control in the ICU has been debated, trials have consistently shown that in post‐operative patients55 and in trauma patients56 improved glucose control with insulin in the intensive care situation has proven beneficial by avoiding complications as long as the deleterious effects of hypoglycaemia are avoided. In the ward situation, intensive insulin treatment is more dubious and hard to control and, therefore, measures should be taken to minimise the insulin resistance and thereby avoiding the need of insulin 53…”
Section: Metabolic Homoeostasismentioning
confidence: 99%
“…A post‐hoc analysis of the NICE‐SUGAR study database20 showed that very strict control leads to moderate and severe hypoglycemia, both of which are associated with an increased risk of death, whereas high incidence of hypoglycemia possibly leads to increased mortality in patients assigned to a group under very strict control.…”
Section: Indication For Intensive Protocol In Critically Ill Patientsmentioning
confidence: 99%
“…This recommendation has been challenged by recent studies suggesting that an even lower target BG is required to prevent SSI 12, 13, 14, 15, 16, 17, 18. The intensive insulin administration protocol (intensive protocol), however, leads to an increased risk of hypoglycemia, which, in turn, is associated with increased morbidity and mortality 19, 20. It seems that very strict glycemic control has modest benefits, with adverse effects often outweighing these advantages in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%